Становлення музейної єгиптології України: лист С.В.Доніча до П.П.Курінного - Романова, О. (Український історичний журнал, 2019)
У науковий обіг уводиться написаний 20 січня 1930 р. завідувачем відділу
«Стародавній Єгипет» Одеського історико-археологічного музею С.В.Донічем
лист до директора Всеукраїнського музейного городка П.П.Курінного, в якому
йшлося про деталі, що виникали у процесі наукового опрацювання колекції давньоєгипетських артефактів, котра на той час зберігалася у Всеукраїнському музейному городку. У поєднанні з низкою інших архівних документів цей лист
дозволяє зробити висновки про спробу започаткувати в Києві в той час осередок із дослідження давньоєгипетських пам’яток. Ініціатором цього процесу став Музей культів і побуту (пізніше перетворений на Музей історії релігії)
та, напевно, саме П.П.Курінний організував як наукове вивчення пам’яток,
так і їх реставрацію. Цьому передувало об’єднання в 1920-х рр. колекцій давньоєгипетських артефактів із трьох музеїв Києва в одну. Це зібрання мало стати потужною джерельною базою для започаткування єгиптологічних
студій у Києві. Як випливає з листа С.В.Доніча, процес наукового вивчення
об’єднаної колекції проводився вже в 1928 р. і він, на той час єдиний єгиптолог на теренах УСРР, брав у ньому участь. До процесу наукового опрацювання давньоєгипетських об’єктів було залучено також російських єгиптологів із
Державного Ермітажу М.Е.Матьє та І.М.Лур’є, про що свідчить листування
цих дослідників із П.П.Курінним, що зберігається в науковому архіві Інституту археології НАН України. Результатом мало стати видання каталогу давньоєгипетських пам’яток Всеукраїнського музейного городка, підготовлене
українською мовою. Утім через «ідеологічні чистки» в музеях, репресії проти
фахівців, запровадження в історичну науку марксистсько-ленінської формаційної теорії, яка обмежувала розвиток історії Стародавнього Світу, і зокрема єгиптології у СРСР, процес організації єгиптологічних студій на території УСРР–УРСР було припинено. The present paper presents the letter of S.Donich, the head of "Ancient Egypt"
department of Odesa Historical and Archaeological Museum, to P.Kurinnyi
(Kurinnyj), the Director of All-Ukrainian Museum Town (Kyiv). The letter was written
in January, 20, 1930, and it contented the details of the academic investigations of
the Ancient Egyptian artefacts’ collection, that resided at the All-Ukrainian Museum
Town at that time. Combined with a number of other archive documents the letter
cause to conclude about attempt to found a center of the Ancient Egyptian objects
studies in Kyiv. It was the Museum of Cults and Everyday Life (later reorganized
into Museum of the History of Religion) that was the institutor of the process, and
P.Kurinnyi appears to have been the organizer of the academic researches of the
Egyptian objects and their restoration as well. It was jointing of the Ancient Egyptian
artefacts’ collections of three Kyiv museums into the one collection during 1920-th,
that preceded the academic researches of the collection. This collection had to become
a sizable basis of primary sources for future Egyptological studies in Kyiv. As it is
evident from Donich’s letter, the process of academic research of the jointed collection
began in 1928. Serhii Donich (who was the only Egyptologist in the territory of
Ukrainian Socialist Soviet Republic at that time) was engaged in the process. Besides
him, two Russian Egyptologists, research associates of State Hermitage M.Matie
(Matthieu, Matthiew) and I.Lurie (Laurie) were engaged in the process of scholarly
observation and investigation of the Ancient Egyptian objects. Their correspondence
with P.Kurinnyi from the Scientific Archive of the Institute of Archaeology, the
National Academy of Sciences of Ukraine proves the participation of the Russian
Egyptologists in the process. The publication of the catalogue of the Ancient Egyptian
objects from the All-Ukrainian Museum Town was planned as the result of the
scholarly research. This edition might be published in Ukrainian. Unfortunately,
this process was stopped due to the policy of All-Union Communist Party (Bolsheviks)
during 1930-th, in particular "ideological cleaning" of the museums, repressions
against Ukrainian intellectuals and intervention of the Marxism-Leninism fiveformations
theory into the academic history, that constrained the development of the
history of Ancient World and Egyptology in the Soviet Union and completely blocked
the development of Egyptology in Ukrainian Socialist Soviet Republic.